Manufacturing productivity analysis by applying overall equipment effectiveness metric in a pharmaceutical industry. Issue 1 (1st January 2021) - Zubair, Muhammad; Maqsood, Shahid; Habib, Tufail; Usman Jan, Qazi Muhammad; Nadir, Uroosa; Waseem, Muhammad; Yaseen, Qazi Muhammad
Abstract: Improving the productivity of a manufacturing firm is very imperative in order to obtain high profits in such a competitive market. Equipment is an important part of a manufacturing system and its efficiency directly affects the quality and cost of the product contributing to overall productivity of a manufacturing plant. This paper focuses on calculating the overall equipment effectiveness (OEE) at a local pharmaceutical industry and investigates the key factors which influence the overall equipment effectiveness. OEE is an important tool which identifies areas that may have bottleneck in the production line, covering three major aspects such as the availability, performance, and quality rate of the output of equipment. On the basis of OEE, six significant losses were identified. The preliminary results of the analysis showed that OEE for the dry suspension (D/S) section is only 23% which is substantially below the benchmark of OEE level i.e. 85%. The results also presented that prime cause involves a high difference between the performance level of world class and dry suspension (D/S) process which is due to unavailability of machines for a longer period of time and malfunctioned machines producing products in large quantities that need to be reworked or scraped. In order to achieve the world class level of OEE, the performance level of dry suspension (D/S) process needs to be enhanced to 95%. A preventive maintenance strategy could be implemented in the industry in order to avoid inefficient practices and enhance the performance of the whole plant.